Socialization of Tempe Home Industry Business in Lebung Gajah Urban Village, Palembang - Nasser, Gamal Abd.; Nisfuriah, Laili; Wati, Asma; Yulianto, Deny; Dali, Dali (Altifani Journal: International Journal of Community Engagement, 2021)
The home industry is a home business product or small company because of the type of economic activity at home. One type of home industry is small industries, including the food industry (food and beverage). Lebung Gajah urban village people generally have a livelihood, primarily workers. Besides, some have small home businesses. This counseling aims to develop human resources and productive efforts based on a strong mental attitude to progress, highly dedicated to the characteristics of his family. The service activity is to provide education on the development of the tempe home industry business. Home businesses of tempeh products have an easier prospect of implementing for small companies because tempe raw materials are easy to get, affordable prices, and delicious. Suppose driven and developed, able to support the family economy, especially in the Village Lebung Gajah, Palembang City, South Sumatra Province.